Strengthening Impact-Oriented Madrasahs: A Critical Analysis of Principal Leadership in Teacher Supervision - Rahmat Yahya; Badrul Mudarris (Al-Qalam Institue, 2026)
This study aims to examine the role of madrasah principal leadership and teacher supervision in shaping instructional quality at Madrasah Tsanawiyah (MTs) NU 2 Maron. Employing a qualitative descriptive approach, the research utilizes empirical data collected through semi-structured interviews with the madrasah principal, supervisory staff, and teachers, complemented by classroom observations and analysis of institutional documents. Data were analyzed using systematic triangulation to ensure credibility and analytical consistency. The findings reveal that the principal’s leadership extends beyond administrative functions toward an instructional orientation characterized by strategic decision-making, clear academic direction, and continuous support for teachers’ professional development. Teacher supervision is implemented as a formative and reflective process rather than a procedural requirement, emphasizing dialogic feedback, reflective practices, and structured follow-up actions that directly influence classroom instruction. These practices result in measurable improvements in teaching strategies, classroom management, and teacher accountability. The study further indicates that strong alignment between leadership vision and supervision practices is crucial for sustaining instructional improvement. The findings imply that leadership development programs for madrasah principals should prioritize instructional leadership competencies and context-sensitive supervision models to enhance learning quality and foster a responsive educational environment that meets students’ academic and developmental needs